An analysis of punishment for baby dumping in Malaysia: a comparative study with the law in Nevada, USA / Nur Azura Mohamad Mansor, Izyan Fasihah Zulkiflee, Melveroline Melton - Mohamad Mansor, Nur Azura; Zulkiflee, Izyan Fasihah; Melton, Melveroline (2014)
This research is pertaining the punishment of baby dumping in Malaysia which is currently a problem and appears to proportionately taking alarm in the society. The growing concern seems to stem from a realisation that despite legal framework, babies are being dumped and abandon and as a result, it leads to the death of the baby. In addition, the research project will be focusing on the effectiveness of the punishment in Section 317 and Section 318 of the Penal Code. An analysis will also be made to see whether the law that has been imposed is adequate in curbing the problem of baby dumping. Hence, the objective of this study is to analyse the sufficiency of the existing law in governing baby dumping, to compare the laws in Malaysia with the laws in Nevada, USA and to propose amendment or appropriate legal framework concerning on baby dumping. This research will also look into the Malaysian Penal Code and the Child Act 2001 as legal authority with regards to this issue. The laws in Nevada, USA will be looked into briefly to understand their legal position pertaining to baby dumping and interesting development of law in that country